Caracterización molecular de mecanismos inflamatorios que contribuyen al desarrollo de miocardiopatía en la enfermedad de Chagas - Cutrullis, Romina (2015)
Chagas disease, caused by the parasite Trypanosoma cruzi, is characterized by an intense inflammatory cardiomyopathy, whose pathophysiology is still not fully understood.\nOur study goal was to examine the contribution of diverse mediators of inflammation to the immunopathogenesis of Chagasic cardiomyopathy and also to evaluate the modulatory effects of etiological treatment with benznidazole on inflammatory agents and heart pathology. We investigated novel potential cardiopathogenic factors that remained unexplored so far (as the proinflammatory cytokine MIF), analyzing its biological significance in experimentally infected animals as well as in Chagas disease patients with different myocardial compromise severity grade.\nThe overall results show that proinflammatory cytokines and chemokines together with their specific receptors participate in immunopathogenic mechanisms leading to chronic Chagasic cardiomyopathy. We focused particularly on the dual role of MIF: displaying key immunoprotective features during the initial steps of T. cruzi infection and, through its persistent induction, also being associated with progression towards the most serious forms of heart dysfunction elicited by prolonged Chagas disease. The immunomodulatory ability exhibited by benznidazol therapy administered during the chronic phase of parasite infection could be helpful in balancing MIF levels and reducing inflammatory injury at this stage, thus limiting the risk of long-term cardiovascular damage.